1998
DOI: 10.1021/bi972761t
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Metabolism of Human Apolipoprotein(a) in Stably Transfected Hep G2 Cells

Abstract: Lipoprotein(a) [Lp(a)] consists of LDL and the glycoprotein apolipoprotein(a) [apo(a)], which are covalently linked via a single disulfide bridge. The formation of Lp(a) occurs extracellularly, but an intracellular assembly in human liver cells has also been claimed. The human apo(a) gene locus is highly polymorphic due to a variable number of tandemly arranged kringle IV repeats. The size of apo(a) isoforms correlates inversely with Lp(a) plasma concentrations, which is believed to reflect different synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 42 publications
3
23
1
Order By: Relevance
“…This conclusion has to be, however, critically evaluated since baboon hepatocytes secrete most of their apoB as VLDL, which does not associate with apo(a) [32]. Similar studies in apo(a)-transfected HepG2 cells could not demonstrate an intracellular apo(a)-apoB assembly for this human hepatocyte model and thus confirmed the results from the baboon studies [24,33,34]. Nevertheless, there is also evidence for intracellular assembly of Lp(a) in cell culture systems.…”
Section: Biosynthesis Of Lp(a)supporting
confidence: 67%
“…This conclusion has to be, however, critically evaluated since baboon hepatocytes secrete most of their apoB as VLDL, which does not associate with apo(a) [32]. Similar studies in apo(a)-transfected HepG2 cells could not demonstrate an intracellular apo(a)-apoB assembly for this human hepatocyte model and thus confirmed the results from the baboon studies [24,33,34]. Nevertheless, there is also evidence for intracellular assembly of Lp(a) in cell culture systems.…”
Section: Biosynthesis Of Lp(a)supporting
confidence: 67%
“…In our previous studies (24,30) as well as in studies reported by others (20), stably transfected HepG2 cells exhibited low synthesis rates for the larger apo[a] isoforms, as evidenced by the extended labeling periods (several hours) required for apo [a] detection in those studies (20). Others have also commented on the lack of suitable models of human liver-derived cell lines expressing apo[a] (22).…”
Section: Inhibition Of Disulfide Bond Formation: Effects Of Apo[a] Sizementioning
confidence: 83%
“…The 13-K4 apo[a] construct was provided by H-J. Müller (20). These expression constructs are annotated (Figs.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations